2018
DOI: 10.1002/2017jd028106
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Anomalous Presummer Extreme Rainfall Over South China and Synoptic Disturbances

Abstract: A spectral analysis of daily rainfall data has been performed to investigate extreme rainfall events in south China during the presummer rainy seasons between 1998 and 2015 (excluding 1999, 2006, 2011, and 2014). The results reveal a dominant frequency mode at the synoptic scale with pronounced positive rainfall anomalies. By analyzing the synoptic‐scale bandpass‐filtered anomalous circulations, 24 extreme rainfall episodes (defined as those with a daily rainfall amount in the top 5%) are categorized into “cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…8d-f) can be traced back to the migratory cyclonic anomalies originated near the southeastern margin of the Tibetan Plateau a few days earlier (Li et al 2014;Huang et al 2018), or are closely related to a deep trough anomaly extending from an intense cyclonic anomaly over north China, which in turn could be traced back to a midlatitude Rossby wave train passing the Tibetan Plateau (Huang et al 2018).…”
Section: The Pre-monsoon-onset Periodmentioning
confidence: 99%
“…8d-f) can be traced back to the migratory cyclonic anomalies originated near the southeastern margin of the Tibetan Plateau a few days earlier (Li et al 2014;Huang et al 2018), or are closely related to a deep trough anomaly extending from an intense cyclonic anomaly over north China, which in turn could be traced back to a midlatitude Rossby wave train passing the Tibetan Plateau (Huang et al 2018).…”
Section: The Pre-monsoon-onset Periodmentioning
confidence: 99%
“…The release will cause a strong negative pressure change at surface, and the wind generated by the pressure change forces the ultra‐low‐level jet to be further strengthened (Gao & Sun, 1984), which is an important mechanism for producing continuous and strong precipitation. The observation and analysis of most PHR events can determine the back‐building/quasistationary (BB) and training line/adjoining stratiform (TL/AS) characteristics (Ding & Liu, 2001; Huang et al., 2018; Luo et al., 2013; Schumacher, 2009; Schumacher & Johnson, 2009; Schumacher & Peters, 2017; Xu et al., 2012), and the quasistationary characteristics are obvious, closely related to the cold pool and associated outflows mainly induced by rain evaporation, which acts as an importance feedback effect for local rainfall with long‐duration (Liu et al. 2018; Wang et al., 2014; M. Wu & Luo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, they indicated that southern YHRB (sYHRB) heavy rainfall resulted from the superposition of quasi-biweekly (10-20-day) and synoptic-timescale disturbances. Following this work, Huang, Luo, and Zhang (2018) also revealed the important contribution of synoptic disturbances to the pre-summer extreme rainfall over South China. Therefore, synoptic-timescale modes should be given equal attention in heavy rainfall studies.…”
Section: Introductionmentioning
confidence: 58%